Residual haptic sensation following stroke using ipsilateral stimulation. Issue 3 (27th June 2007) - Valentini, M; Kischka, U; Halligan, P W
Abstract : In 1987, Weiskrantz and Zhang described a stroke patient with severe somatosensory loss who, nevertheless, demonstrated impressive residual sensory performance when required to touch the affected limb with her ipsilesional hand (self touch; ST). The current study set out to ascertain the prevalence and characteristics of self-touch enhancement (STE) in patients with unilateral stroke and hemihypaesthesia. Thirty-nine stroke patients who were referred with hemihypaesthesia fulfilled the criteria. STE was defined where a patient showed a statistically significant increase (p<0.05) in performance for (i) detection, (ii) localisation and/or (iii) perceived intensity during touch with their ipsilesional hand, compared with standard experimenter elicited sensory performance. Group comparisons between the conventional touch versus ST conditions revealed significant differences for detection (p<0.01), intensity estimation (p<0.01) and localisation (p<0.001) using ST. Twenty-two of the 39 patients (56.4%) showed STE on at least one assessment mode. In detection, 16 (41%) patients showed STE; for localisation, 12 patients (31%) showed STE and for intensity, 17 patients (44%) showed STE. Out of the 22 patients with STE, 17 had right hemisphere lesions. In summary, more than half of the stroke patients showed reliable and significant improvements in somatosensory performance when using their unaffected hand as the source of tactile stimulation. This striking phenomenon suggests that the threshold for the impaired hand is affected by active involvement of the contralateral (ipsilesional) limb when delivering the stimulus contact. Possible mechanisms to explain these findings are discussed.